Plastic strain distribution throughout the microstructure duality during the fracture process of non-combustible Mg products fabricated by selective laser melting. (December 2020) - Proaño, Bryan; Miyahara, Hirofumi; Matsumoto, Toshiharu; Hamada, Shigeru; Sakai, Hitoshi; Ogawa, Kiyoshi; Suyalatu; Noguchi, Hiroshi
Highlights: Several Mg-9%Al-2%Ca alloy specimens were made using selective laser melting process. Tensile testing was interrupted at 90% of the ultimate strength value. Length of the stable propagation area of the crack was verified by EBSD analysis. Dispersed plastic strain localized in the outside regions of the meltpool formations. A dispersed plastic strain enhances fracture toughness of SLM products in as-built conditions. Abstract: In this study, several Mg-9%Al-2%Ca alloy round-bar specimens were fabricated by the selective laser melting (SLM) process. A fraction of the specimens was submitted to tensile testing. Then, the remaining fraction of specimens were drilled and subsequently submitted to further tensile testing interrupted at 90% of the ultimate tensile strength (UTS). Fracture surfaces were analyzed and an Electron Backscatter Diffraction (EBSD) analysis was performed to observe plastic strain. The results showed a dispersed plastic strain distribution that concentrated at the coarse grain microstructure, specifically at the outer regions of each melt pool formation. Microstructure coarsening is an intrinsic phenomenon of the SLM processes and induces crack arrest during the transition from a stable fracture to an unstable fracture. Accordingly, fractography results showed a large flattened area in the fracture surface, which suggests a stable and propagating plastic strain beneath the fracture surface, but no crack propagation of the corresponding length was found, despite interrupting the test at 90% of the UTS value. Based on this information, an indicator that evaluates plastic strain as continuous or discontinuous could be used in order to explain the high tensile strength and fracture behavior of SLM products in as-built conditions, which have been discussed but not verified to date.